Postharvest intake potential of pathogenic microorganisms in fruit structures - Davidovich-Young, Gabriela (2024)
Introduction. In recent years, there has been an increase in the consumption of fresh agricultural products, raising concerns about foodborne outbreaks related to these products due to the incorporation of pathogenic microorganisms into the fruits. The aspects related to this incorporation have been studied in some fruits; however, not everything associated with this issue has been clarified. Objective. To investigate and summarize the incorporation of pathogenic microorganisms into fruit structures. Development. This work was conducted in Costa Rica between July 2021 and September 2022. It contrasts the definition of internalization and infiltration and describes the conditions that favor the incorporation of pathogenic microorganisms into fruit, as well as the routes and distribution patterns of the incorporated microorganisms. Control strategies to prevent the incorporation of pathogens into these structures are also discussed. Conclusion. Most research on the incorporation of pathogenic microorganisms into fruits focuses on a few products and yields diverse and sometimes contradictory results. It is pertinent to direct future research towards evaluating the phenomenon under conditions closer to those of commercial operations of interest and to reinforce strategies that ensure the proper implementation of good agricultural practices and good manufacturing practices.